Exploration of the Structure-Function Relationships of a Novel Frog Skin Secretion-Derived Bioactive Peptide, t-DPH1, through Use of Rational Design, Cationicity Enhancement and In Vitro Studies - Haixin Qin; Hantian Fang; Xiaoling Chen; Lei Wang; Chengbang Ma; Xinping Xi; Tianbao Chen; Chris Shaw; Mei Zhou (MDPI AG, 2021)
Amphibian skin-derived antimicrobial peptides (AMPs) have attracted increasing attention from scientists because of their excellent bioactivity and low drug resistance. In addition to being the alternative choice of antibiotics or anticancer agents, natural AMPs can also be modified as templates to optimise their bioactivities further. Here, a novel dermaseptin peptide, t-DPH1, with extensive antimicrobial activity and antiproliferative activity, was isolated from the skin secretion of Phyllomedusa hypochondrialis through 'shotgun' cloning. A series of cationicity-enhanced analogues of t-DPH1 were designed to further improve its bioactivities and explore the charge threshold of enhancing the bioactivity of t-DPH1. The present data suggest that improving the net charge can enhance the bioactivities to some extent. However, when the charge exceeds a specific limit, the bioactivities decrease or remain the same. When the net charge achieves the limit, improving the hydrophobicity makes no sense to enhance bioactivity. For t-DPH1, the upper limit of the net charge was +7. All the designed cationicity-enhanced analogues produced no drug resistance in the Gram-negative bacterium, Escherichia coli. These findings provide creative insights into the role of natural drug discovery in providing templates for structural modification for activity enhancement.